THE USE OF THE DRASTIC METHOD AND GIS IN ASSEESSING THE VULNERABILITY OF THE GROUNDWATER, IN THE VELIPOJA -ZADRIMA AQUIFER, ALBANIA - Bele, S. (Bulletin of the Geological Society of Greece, 2016)
The Albanian plain area is densely populated. The population doubled during the last two decades and most of it uses the groundwaters of these aquifers. Aquifers in lowland areas are vulnerable to pollution. This article assesses the vulnerability of groundwater Velipoj-Zadrimè aquifer. This aquifer has a surface of 237 km2 and an average height of 10m above sea level. Groundwater recourses are connected with alluvial deposits formed by Drini and Buna rivers. The vulnerability Map is an ιmportant tool for the management of the territory. It guides the selection of areas for development projects, in order to avoid negative consequences on the quality of groundwater. Geographic Information Systems are very valuable programme for processing. The DRASTIC method has been used to map the natural aquifer vulnerability of the Velipoja-Zadrima study area. This method, applied to assess the vulnerability of the aquifer, was developed by the "Environmental Protection Agency (US EPA)" and "The National Association of Water Wells (NWWA)". It is a technique to assess the potential contamination of groundwater and is based on seven (7) parameters: Depth (D), Recharge (R), Aquifer media (A), Soil media (S), Topography (T), Impact of vadose zone (I), and Conductivity of the aquifer (C). The DRASTIC index is determined by the sum of the products of the Weight and site ratings of all the parameters. High values of vulnerability cover large areas of the aquifer. The results provide important information for local authorities in the management of resources and territory.